Exploring the Mechanical Behavior of Concrete enhanced with Fibers derived from recycled Plastic Bottles - Abdulateef, Lana Ayad; Hassan, Sara Hikmat; Ahmed , Ahmed Mohamed (Engineering, Technology & Applied Science Research, 2024)
The increasing issue of plastic waste has become detrimental to human society, particularly with the increase in disposable plastic bottles in many countries. This study investigates the impact of incorporating plastic bottle waste fibers on the slump, density, compressive strength, split tensile strength, and flexural strength of concrete. This material was selected for its cost-effectiveness and wide availability, addressing the prevalent global concern of environmental pollution resulting from inadequate waste management practices. This study describes a systematic plan to fabricate and test cubes, cylinders, and beams using Fiber-Reinforced Concrete (FRC). A comparative analysis was performed between concrete reinforced with plastic bottle waste fibers, in varying ratios of 1, 2, and 3%, and plain concrete. The results showed a positive impact on concrete strength with fiber addition, although at the expense of reduced workability and decreased concrete density. In particular, a significant improvement in the ductility of the concrete was observed. The analysis shows that a fiber ratio of 2% emerges as the most optimal dosage to achieve improved concrete properties. This study provides valuable insights into the imperative pursuit of sustainable concrete production and the environmental challenges posed by plastic waste.